Electronic packaging assembly concept for computer casing - Wee, Yap San. (2008)
New processor and software developments are appearing with ever increasing frequency on the market. Resistance to impact, vibration and temperature as well as short assembly times are necessary for efficient production. Due to the steadily increasing demand, computer systems must be frequently enhanced which costs both time and money. However, the physical design of the PC has changed little to keep up with this transition in technology. Today, many PC users and manufacturer desire PC systems that maintain the highest level of performance yet are easy to produce, low platform cost, quieter to fit more easily into users lifestyles.